Research for Practice: The Fun in Fuzzing. - NAGY, STEFAN (Communications of the ACM, 2023)
The article presents information on software fuzzing, a process used for automated bug and vulnerability testing. Several papers are cited and discussed by Stefan Nagy, an assistant professor at the University of Utah. Software fuzzing uses new and unexpected inputs which are systematically generated in order to test programs. The cited papers provide information on topics such as specific classes of bugs and finding bugs in compilers, demonstrating the advantage of combining traditional testing methods with innovative techniques and machine learning in order to identify bugs in complex software systems.